Optimization of twin vertical axis wind turbines through large eddy simulations and Taguchi method. (1st February 2022) - Peng, H.Y.; Liu, M.N.; Liu, H.J.; Lin, K.
Abstract: The aerodynamic performance of twin configurations of vertical axis wind turbines (VAWTs) was systematically analyzed through large eddy simulations (LESs). The reliability of the computational results was validated through comparisons with experimental data reported in the literature. The Taguchi method was used in the optimization analysis, and an L16 (4 5 ) orthogonal table of five critical operation parameters—pitch angle ( β ), turbine spacing ( S / D ), aspect ratio ( η ), solidity ratio ( σ ), and rotational direction ( γ )—with four levels was designed. Range analysis was applied to the results of the orthogonal test. Pitch angle was found to have the greatest extent of impact on power performance, whereas rotational direction exerted the least impact. Additionally, turbine spacing exercised the second greatest impact, followed by aspect ratio and thence solidity ratio. Accordingly, the parameter settings for the optimal and the worst twin array units were determined. The power performance of the optimal and worst twin array units increased by 13.72% and 7.39%, respectively, relative to their standalone counterparts. Moreover, analyses of the flow mechanisms indicated that to reduce power loss, tip winglets or tapered blade ends should be used in twin array units, especially those with small aspect ratios. Highlights: Twin unit of VAWTs are systematically analyzed through LES and Taguchi method. Extent of impact ranks: pitch angle ˃ distance ˃ aspect ratio ˃ solidity ratio ˃ rotation direction. Increases of 13.7% and 7.4% in C P in optimal and worst array units, respectively. Optimal twin unit experiences larger gradients of velocity and pressure than worst one. Tip vortices are more violent than and are susceptible to interference by span vortices.